A structure-based proposal for a comprehensive myotoxic mechanism of phospholipase A2-like proteins from viperid snake venoms - Fernandes, Carlos A. H. (2014)
artículo (arbitrado) -- Universidad de Costa Rica, Instituto Clodomiro Picado. 2014. Este documento es privado por restricciones de derechos de autor